Smoking cessation: An acrobatic jump (Portuguese Journal of Family Medicine and General Practice, 2012)
Introduction: Smoking cessation is like an acrobatic jump. The general practitioner has the opportunity to create the running track (in successive appointments), to provide a trampoline (specific therapy) and then watch the athlete (the smoker) jump over (smoking cessation) the bar (dependence). Case Description: The patient was a 46 year-old female smoker. She came to a smoking cessation consultation. She was mo- tivated to quit smoking and had a Fagerström score of 5 points. She was caring for her mother, who was a patient with pul- monary adenocarcinoma. The patient stated that her mother's condition was the main reason for smoking cessation. She star- ted treatment with varenicline. With failure of treatment, she came back for a family assessment. She had been abandoned by her mother when she was 6 years-old and said that "I feel tremendously guilty. I have no compassion for her suffering". After brief psychotherapy, the patient stopped smoking two months later. Comment: This case shows the diagnostic and therapeutic potential of family assessment in smoking cessation. The initial fai- lure of treatment raised the suspicion there was something else that kept the patient from regaining balance. Telling her life story resulted in therapeutic communication between the patient and her doctor. This assessment detected a latent anxiety disorder, which was making it hard for the patient to quit smoking.
Keywords: Smoking Cessation; Family Assessment; Counseling